PMMB COVID-19 Bulletin: United Kingdom (22nd April 2020) - Loh Teng-Hern Tan; Vengadesh Letchumanan; Hooi-Leng Ser; Jodi Woan-Fei Law; Nurul-Syakima Ab Mutalib; Learn-Han Lee (Progress in Microbes and Molecular Biology)
COVID-19 has greatly impacted the world and posed an enormous public health threat. The United Kingdom is hit harder by the COVID-19 crisis than any other European countries, besides Italy, Spain and France. The UK government has come under heavy criticism for its response to COVID-19, with lack of preparedness, shortages of personal protective equipment and COVID-19 testing. Despite the lockdown is in place to slow the spread of COVID-19, UK death toll continues to surge. As of 21st April 2020, more than 120,000 confirmed COVID-19 cases and 16,000 deaths had been recorded in UK.